Implementation of electronic health records systems in surgical units and its impact on performance. Issue 10 (30th July 2019) - Liu, Zhen Yu; Edye, Michael
Abstract : Background: Electronic health records (EHR) systems have been utilized in New South Wales for more than a decade; however, there is no agreement as to what clinical benefits they provide. This study aims at determining whether the introduction of EHR systems resulted in changes in documentation quality and other markers of clinical performance such as post‐operative length of stay (PO LOS), use of imaging modality, rates of readmission and morbidity. Methods: A before and after study was conducted utilizing both written and electronic patient documentation in a single surgical ward. Patients who underwent appendicectomy at Blacktown Hospital had inpatient documentation collated at three distinct time‐points. Documentation was then assessed against the QNOTE assessment criteria. Other markers of clinical performance assessed included PO LOS, ultrasound use, computed tomography use, rate of readmission, rate of morbidity and rate of positive histological findings. Results: There was a significant ( P = 0.001) improvement in QNOTE score between group 1 (6 months prior to the implementation of EHR) and group 3 (12 months after the implementation of EHR) of 9 points. PO LOS was reduced following the implementation of EHR from 1.94 to 1.37 days ( P = 0.001). Conclusion: This study demonstrated that following the implementation of EHR system in an inpatient surgical ward, notation quality improved. It was also found that the implementation of EHR was associated with a decrease in PO LOS. Abstract : The advent of electronic health record systems in Australia may increase hospital efficiencies and decrease length of stay in the setting of acute appendicitis.